(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to demonstrate the importance of leadership empowerment in its dimensions (knowledge, participation in decision-making, incentives, trust between the leader and subordinate, delegation of authority and communication) and its impact on enhancing the effectiveness of the company in its dimensions Represented by (achievement of objectives, quality of insurance service, adaptation to work environment and job satisfaction), by adopting the questionnaire as a main tool in collecting data from officials in the National Insurance Company, numbering (56) surveyed in job sites (section manager, division official and unit official) Their answers were analyzed using the SPSS statistical program in calculating the arithmetic mean, standard deviation, relative importance, a test F and coefficient of determination R2, and the most prominent results were: There is a positive attitude among the surveyed sample regarding the dimensions of leadership empowerment and enhancing the effectiveness of the company to a high degree. There is a significant effect of leadership empowerment in enhancing the effectiveness of the company under study, and it reached a rate of (70%).